Low red blood cell predicts high risk of temporary postoperative complications after carotid body tumor surgical resection - Han, Tonglei; Wang, Shiying; Zhu, Jiang; Sun, Yudong; Xie, Yongfu; Wei, Xiaolong; Zhou, Jian; Zhao, Zhiqing (Frontiers in Oncology, 2022)
Background: Carotid body tumor (CBT) is a rare paraganglioma located at the carotid bifurcation. The red blood cell count, hemoglobin and hematocrit are indexes to be evaluated in blood routine tests. The purpose of this study was to clarify their predictive value for temporary postoperative complications in patients that had undergone CBT surgery. Methods: This retrospective trial included data from 169 patients received surgical treatment for CBT from October 2008 to September 2018 in this retrospective study. Postoperative follow-up was conducted under the guidance of both vascular surgeon and neurologist. The symptoms existed less than two years postoperatively were regarded as temporary injuries. The red blood cell count, hemoglobin and hematocrit were obtained from the complete blood count results of the participants. Analyses of multilevel multivariable regression and descriptive statistics were conducted. Results: The baseline data showed no significant difference. Patients were predominantly female (53.8%), with a mean age of 42.6 years. The total incidence of temporary postoperative complications was 22 (13.0%), included: transient ischemic attack (8, 4.7%), tongue bias (7, 4.1%), dysphagia (2, 1.2%), hoarseness (4, 1.8%), eyelid ptosis (1, 2.4%). The univariate and multivariate regression analysis results revealed that the occurrence of temporary postoperative complications was increased with age (OR, 0.09; 95% CI, 0.9-1.0; P=0.014), length of operation time (OR, 1.0; 95% CI, 1.0-1.0; P=0.005), Shamblin type II vs. I (OR, 0.1; 95% CI, 0.0-0.5; P=0.008), red blood cell count postoperative (OR, 0.2; 95% CI, 0.1-0.8; P=0.026), hemoglobin (OR, 0.9; 95% CI, 0.9-1.0; P=0.011) and hematocit (OR, 0.8; 95% CI, 0.7-1.0; P=0.025). The smooth curve fitting showed that the trend of complications occurrence rate was reduced with the increase of patients’ postoperative red blood cell count, hemoglobin and hematocrit. Gender, weight, length of operation, Shamblin type, postoperative red blood cell count, hemoglobin and hematocrit were included in the risk model with AUC=0.86. Conclusion: These CBT patients who received surgical ressection with low postoperative red blood cell, hemoglobin, or hematocrit had a high risk of temporary postoperative complications. The risk prediction model setablished for predicting temporary postoperative complications showed satisfactory prediction effects.